Primary Carcinoid Tumor of the Urinary Bladder A Case Report and Questionnaire Survey on the Reported Cases in Japan - Ueda, Norichika (Hinyokika kiyo. Acta urologica Japonica, 2015)
An 83-year-old man presented with asymptomatic macroscopic hematuria while being treated for prostate cancer with hormonal therapy in January 2009. Cystoscopy revealed a 5 mm surface-smooth non pedunculated tumor lateral to the left ureteral orifice. Transurethral resection was carried out to examine the histology of the tumor. Histopathologic examination revealed the tumor arranged in a pseudoglandular pattern covered with erosive urothelial cells. The tumor had inconspicuous nucleoli, and abundant eosinophilic cytoplasm. An immunohistochemical study showed the tumor cells were positively stained for chromogranin A, synaptophysin, CD56, and NSE. Ki67 index of the tumor was below 2 %, indicating that the tumor was a carcinoid tumor. He showed no carcinoid syndrome, and neither recurrence nor metastasis has been detected for 66 months